The seeing stone - DiTerlizzi, Tony.; Black, Holly (New York Simon & Schuster Books for Young Readers, 2003)
When Mallory and Jared attempt to rescue Simon from goblins, they use a magical stone which enables them to see things that are normally invisible.
In which more than a cat goes missing -- In which several things are taken, including a test -- In which Mallory finally gets to put her rapier to good use -- In which Jared and Mallory find many things, but not what they are looking for -- In which the fate of the missing cat is discovered -- In which Jared is forced to make a difficult choice -- In which Simon outdoes himself and finds an extraordinary new pet.
Sequel to: The field guide.
Keywords: Goblins -- Fiction; Brothers and sisters -- Fiction; Single-parent families -- Fiction; Fairies -- Juvenile literature